(untitled) (Global Journal of Human-Social Science, 2014)
The purpose of the study was to explore the relationship between resilience, psychological distress and subjective well-being among the survivors of dengue fever. It was hypothesized that there would be significant relationship among resilience, psychological distress and subjective well-being among the dengue fever. It was correlation study in which cross-sectional research design was used. The sample size was one hundred (N=100) survivors which comprises of fifty male and fifty female dengue survivors. The sample was drawn by using purposive sampling strategy which is a technique of nonprobability sampling because it is the nature of population which is survivors so this type of sampling is helpful for recruit sample in the study. Three scales Trait Resilience Checklist (Hiew, et al 2000), Psychological Distress Scale (Kessler, et al 1992) and Subjective Happiness Scale (Lyubomirsky, 1999) were used to measure resilience, psychological distress and subjective well-being respectively. SPSS-20 was used to run statistical analyses. The results showed that there is significant positive correlation between resilience and subjective well-being among survivors of dengue fever. Moreover, there is significant negative relationship exist between psychological distress and subjective well-being, and between resilience and psychological distress.